The Disenchantment of Democracy in Peru - Pozo Tinoco, Johel Miguel (2022)
The current public acknowledgment is that we live under a democratic regime, but at the same time there is a remarkable discontent about its efficiency. The specialized literature has multiple criteria for defining democracy, which allows to address aspects of it such as the legal framework, the election system, the participation processes, and the fundamental rights and human rights. Despite this richness of contents, here in the country prevails a procedural approach that emphasizes the electoral processes and neglects others that are of paramount importance to democratic quality or satisfaction regarding democracy as such. From this discontent we can identify criticism arising from political theory and from the same actors who, in the face of the problems of democracy, propose more democracy. But we also find criticism that in questioning existing procedural democracy challenge fundamental issues as well, some structural ones, such as modernity, the institutional design of the unitary state, minority rights, equal opportunities, among other aspects of current significance. One of these criticisms will be called enlargement reviews; and the other, breakup reviews. Both offer opportunities to improve the democratic regime and call for a forward-looking approach.